GIANT CELL TUMOUR OF THE OCCIPITAL BONE IN A 13-YEAR OLD MALE - Chugh, Ashish; Mohapatra, Ashutosh; Punia, Prashant; Gotecha, Sarang Shirish; Choudhury, Priyam (Journal of Ayub Medical College Abbottabad, 2022)
Giant Cell Tumours (GCT) are usually found at the extremities of the long bones and their presence in the skull being less than 1%. In the skull, sphenoidal bone and temporal bone are the commonest sites. There have been very few reports of GCTs of the occipital bone. Total excision surgery is the ideal treatment of choice. If surgery poses a problem, then adjuvant radiotherapy can be administered too. We present a case of 13-year-old male child who was diagnosed with GCT of the occipital bone. He was successfully operated and is symptom free 6 months post his surgery till now.